2009
DOI: 10.1111/j.1365-2761.2008.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular redescription of the myxozoan Unicapsula pflugfelderiSchubert, Sprague & Reinboth 1975 from two teleost hosts in the Mediterranean. A review of the genus Unicapsula Davis 1924

Abstract: Elongate plasmodia with myxosporean spores belonging to the genus Unicapsula, Davis, 1924 were found in the skeletal muscle of the striped seabream, Lithognathus mormyrus (L.), a candidate for the mediterranean aquaculture. The only species of Unicapsula described from the Mediterranean is Unicapsula pflugfelderi Schubert et al. 1975, which occurs in the picarel, Spicara smaris (L.). For morphological and molecular comparison of U. pflugfelderi from S. smaris with Unicapsula sp. from L. mormyrus measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The vesicular body observed in the present study was previously reported in Unicapsula pflugfelderi where vesicles measured 40–60 nm. In U. pflugfelderi the vesicular body was also found in close vicinity to developing polar capsules, and a secretory function was suggested [60]. Due to its location and its vesicular structure it is suggested that the presence and function of the vesicular body is related to capsulogenesis, possibly secreting carbohydrates or other substances required for polar capsule formation.…”
Section: Discussionmentioning
confidence: 99%
“…The vesicular body observed in the present study was previously reported in Unicapsula pflugfelderi where vesicles measured 40–60 nm. In U. pflugfelderi the vesicular body was also found in close vicinity to developing polar capsules, and a secretory function was suggested [60]. Due to its location and its vesicular structure it is suggested that the presence and function of the vesicular body is related to capsulogenesis, possibly secreting carbohydrates or other substances required for polar capsule formation.…”
Section: Discussionmentioning
confidence: 99%
“…Spores were observed using Nomarski differential interference contrasting illumination at magnification of ×200–1600, using oil immersion to study and describe the morphology of mature spores. Several photomicrographs were obtained using Olympus CellDimension© imaging software to obtain measurements of mature spores according to Alama-Berjamo et al ( 2009 ). In addition, spore apical length and width were obtained as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the genus Unicapsula (Davis 1924) are multivalvulids belonging to the family Trilosporidae, which accommodate myxosporean parasites that have three valves, each bearing a polar capsule (Lom and Dykova 2006 ). Unicapsula species are unique among other Trilosporidae because only one of the three polar capsules is fully developed and functional, whereas the remaining two are rudimentary and barely visible (Alama-Berjamo et al 2009 ; Miller and Adlard 2013 ). Since the description of the genus and the type species in 1924 by Davis, a total of 12 species of Unicapsula have been recorded from different localities and a wide range of marine host species (Naidjenova and Zaika 1970 ; Schubert et al 1975 ; Sarkar 1984 ; Sarkar 1999 ; Diebakate et al 1999 ; Miller and Adlard 2013 ; Tomochi et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some spore preparations were fixed in methanol and incubated with DAPI overnight to be able to count the number of sporoplasms in the spores. Lysine-coated coverslips with spores were fixed in 2.5% glutaraldehyde and processed for scanning electron microscopy (SEM) as described in Alama-Bermejo et al (2009). For molecular analyses, blood obtained from the caudal vein and small kidney pieces of each fish were fixed in 100% ethanol.…”
Section: Methodsmentioning
confidence: 99%